IIMPLEMENTASI KEGIATAN DZIKIR PAGI DAN PETANG DAN PERANNYA DALAM MEMBENTUK KECERDASAN SPIRITUAL SANTRI PONDOK PESANTREN (Penelitian Pada Santri Pondok Pesantren Persatuan Islam Al-Amin Sindangkasih Kab. Ciamis) - kholis (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2024)
Education is still a public conversation today, seeing various issues of public unrest with the decline in the quality of the younger generation, the globalization era which should have a good influence but in reality it has a bad impact, one of the causes is the lack of spiritual and spiritual education for the younger generation, so a habituation of an activity to shape children's spirituality is carried out in boarding school institutions that can have a positive impact on students. The purpose of this study was to determine the implementation of morning and evening dhikr at Persis Al Amin Islamic Boarding School in shaping the spiritual intelligence of students as well as the supporting and inhibiting factors for the implementation of morning and evening dhikr. This research uses a descriptive qualitative method approach. The results of the study are 1) The implementation of morning and evening dhikr at Pesantren Persis Al Amin is carried out every day in the morning and evening. The stages of implementation are first reading the Ayat kursi, Al-Ikhlas, Al-Falaq, An-as, both morning and evening prayers. The habituation of morning and evening dhikr consistently aims to shape the spirituality of students as a rabbani generation. 2) The behavior of students before the morning and evening dhikr has low spirituality, as evidenced by the fact that there are still students who are lazy to worship, emotional, anxious, do not understand the meaning of life, ambitious, and behavior below reasonable limits. But the spiritual condition of the students changed after implementing the morning and evening dhikr. They become calm, patient when facing trials and become obedient to Allah. Always remembering Allah in everything they do, especially in seeking knowledge. 3) The implementation of morning and evening dhikr activities at Pesantren Persis Al Amin has supporting and inhibiting factors, among the supporting factors are the existence of morning and evening dhikr books distributed by pesantren for students, making it easier to implement morning and evening dhikr to encourage students to read morning and evening dhikr, and the participation of ustadz in the implementation of morning and evening dhikr. While the inhibiting factor is the delay of the ustadz so that the implementation is delayed, the facilities that are not good for the implementation of morning and evening dhikr, and the obstacles of students who do not participate in activities